2007
DOI: 10.1161/circulationaha.106.668756
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-Ribose) Polymerase Inhibition Reduces Atherosclerotic Plaque Size and Promotes Factors of Plaque Stability in Apolipoprotein E–Deficient Mice

Abstract: Background-Poly(ADP-ribose) polymerase (PARP) was suggested to play a role in endothelial dysfunction that is associated with a number of cardiovascular diseases. We hypothesized that PARP may play an important role in atherogenesis and that its inhibition may attenuate atherosclerotic plaque development in an experimental model of atherosclerosis. Methods and Results-Using a mouse (apolipoprotein E [ApoE]Ϫ/Ϫ ) model of high-fat diet-induced atherosclerosis, we demonstrate an association between cell death and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
138
1
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(157 citation statements)
references
References 30 publications
9
138
1
9
Order By: Relevance
“…These conclusions were drawn from studies where factors that promoted atherosclerosis, such as oxidized LDL, hyperglycemia, and H 2 O 2 -stimulated PARP activity (47)(48)(49)(50). PARP-1 was activated within atherosclerotic plaques of ApoE Ϫ/Ϫ mice fed a high fat diet (51). PARP-1 deletion, on the other hand, reduced atherosclerotic lesion formation in high fat diet-fed ApoE Ϫ/Ϫ mice (52), and PARP catalytic inhibitors reduced atherosclerotic plaque burden in mouse models of atherosclerosis (53).…”
Section: Discussionmentioning
confidence: 99%
“…These conclusions were drawn from studies where factors that promoted atherosclerosis, such as oxidized LDL, hyperglycemia, and H 2 O 2 -stimulated PARP activity (47)(48)(49)(50). PARP-1 was activated within atherosclerotic plaques of ApoE Ϫ/Ϫ mice fed a high fat diet (51). PARP-1 deletion, on the other hand, reduced atherosclerotic lesion formation in high fat diet-fed ApoE Ϫ/Ϫ mice (52), and PARP catalytic inhibitors reduced atherosclerotic plaque burden in mouse models of atherosclerosis (53).…”
Section: Discussionmentioning
confidence: 99%
“…Stained slides were scanned using the ×40 objective with a Hamamatsu NanoZoomer (Hamamatsu, Bridgewater, NJ, USA). Immunoreactivity was analyzed by using Image-Pro Plus Version 6.0 software (Media Cybernetics, Rockville, MD, USA) as described previously (9,10). The measurement parameters included density mean, area sum and integrated optical density.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…For immunofluorescence, cells were seeded on chamber slides and treated as described in the figure legends. Cells were then fixed, permeabilized and stained with antibodies to PDZK1 (Abcam, Cambridge, MA, USA) and with 4′-6-diamidino-2-phenylindole essentially as described (10). Cells were then examined with a Nikon fluorescence microscope.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…57 An imbalance of tissue inhibitor of metalloproteinases and matrix metalloproteinases in the extracellular matrix may constitute a critical contributing factor to atherogenesis. Boulares and coworkers 58,59 found that PARP-1 inhibition provides stability to atherosclerotic plaques associated with increased expression of tissue inhibitor of metalloproteinases 2, decreased activity of matrix metalloproteinase 9, and extracellular matrix degradation in a high-fat, diet-induced, dyslipidemic, dilated cardiomyopathy model. Rheumatoid arthritis is characterized as inflammation with synovial hyperplasia, pannus formation, and progressive destruction of cartilage and bone.…”
Section: Involvement Of Parp-1 In Inflammatory Diseasesmentioning
confidence: 99%